FEATURE AND SERVICE QUALITY IMPROVEMENT OF JENIUS DIGITAL BANK USING TEXT MINING METHOD - Ramadhan Sugiantoro, Nivan
The high development of the internet and technology also impacts banking with the existence of digital banking. Jenius has problems with poor online reviews. To maintain its existence in the digital industry and maintain customer loyalty, Bank Jenius tries to take advantage of customer reviews to improve the features and quality of its services. This study tries to reveal public sentiment, public opinion, and service quality as reflected in the Google Play review of the Jenius application. Public sentiment analysis and service quality analysis are carried out using a sentiment analysis classification algorithm. Public opinion is done by using topic modeling using the LDA algorithm.